2013
DOI: 10.1080/10934529.2013.730390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of test media on reproduction inPotamopyrgus antipodarumand of pre-exposure population densities on sensitivity to cadmium in a reproduction test

Abstract: Molluscan species can be affected by various anthropogenic substances. Yet, these effects are disregarded in chemical risk assessment as molluscs are unrepresented in standard OECD guidelines. The project "validation of a mollusc reproduction test" (Federal Environment Agency, code 371165417) deals with the development of a test method with the mudsnail Potamopyrgus antipodarum for OECD purposes. In this context, the influence on reproduction of both, different media and varying snail density, has been observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Profound effects of population density on embryo production were even observable between treatments differing in density by only one snail, exemplified by the ∼162% higher embryo production of individuals in the seven-snail treatment relative to individuals in the eight-snail treatment. While another recent study of the influence of population density on reproduction in P. antipodarum also showed that reproductive output increased at intermediate densities [13] , our study is the first to show that this phenomenon occurs in the absence of systematic changes in food availability across density treatments.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Profound effects of population density on embryo production were even observable between treatments differing in density by only one snail, exemplified by the ∼162% higher embryo production of individuals in the seven-snail treatment relative to individuals in the eight-snail treatment. While another recent study of the influence of population density on reproduction in P. antipodarum also showed that reproductive output increased at intermediate densities [13] , our study is the first to show that this phenomenon occurs in the absence of systematic changes in food availability across density treatments.…”
Section: Discussionsupporting
confidence: 58%
“…Here, our goal was to provide an in-depth characterization of the relationship between population density, growth rate, and reproductive output in P. antipodarum . Our main points of departure from similar studies conducted by Neiman et al (2013) [11] and Sieratowicz et al (2013) [13] are 1) the combined use of a wide range of population densities and precisely controlled food administration, 2) individual-level variation in population density, and 3) the inclusion of two genetically distinct lineages. Because growth and reproduction in P. antipodarum is very sensitive to food availability [11] , parsing out direct effects of population density requires that food availability does not vary across density treatments.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations